Explaining Andean exogamy: A tentative model - Bolton, Ralph (1973)
Anthropologists have preferred to concentrate on the analysis of societies and their cultures as units taken out of the context of their external relations, thus ignoring the valuable body of data that could make important contributions to the understanding of each society, analyzing in such a way that the emphasis would be placed on understanding the total context in which society operates. While early anthropological methods were adequate for the study of isolated communities and primitive nomadic bands, they are not adequate for the investigation of more complete societies.